Fiber reinforced composite and surface coated esthetic archwires: a review - GVD, Harsha; M, Anoosha; K, Pradeep; CV, Padmapriya; M, Ravi Varma; RS, Usha Sree (International Journal of Dental Materials, 2020)
Orthodontic treatment has undergone a drastic transformation for a few years. Many patients present with a set of challenges to orthodontists in terms of esthetics while undergoing orthodontic treatment. The introduction of composite & ceramic brackets has led to the development of esthetic archwires to meet the increased demand for esthetics during orthodontic treatment. This article discusses various widely used esthetic archwires used in orthodontic treatment.